Cellular and Subcellular Contact Guidance on Microfabricated Substrates - Leclech, Claire; Villard, Catherine (Frontiers in Bioengineering and Biotechnology, 2020)
Topography of the extracellular environment is now recognized as a major determinant of cell behavior and function. The study of cell-topography interaction, named contact guidance, has greatly benefited from the development of micro and nano-fabrication techniques, allowing the emergence of increasingly diverse and elaborate engineered platforms. The purpose of this review is to provide a comprehensive view of the process of contact guidance from cellular to subcellular scales. We first classify and illustrate the large diversity of topographies reported in the literature by focusing on generic cellular responses to diverse topographical cues. Subsequently, and in a complementary fashion, we adopt the opposite approach and highlight cell type-specific responses to classically used topographies (arrays of pillars or grooves). Finally, we discuss recent advances on the key subcellular and molecular structures involved in topographical sensing. Throughout the review, we focus particularly on neuronal cells, whose unique morphology and behavior have inspired a large body of studies in the field of topographical sensing and revealed fascinating cellular mechanisms. We conclude by using the current understanding of the cell-topography interactions at different scales as a springboard for identifying future challenges in the field of contact guidance.